Constraints Faced by the Students in the Usage of ICT Initiatives in Agricultural Education (Indian Journal of Extension Education, 2021)
Information and communication technologies (ICTs) play a pivotal role in all aspects of our lives in a rapidly growing information society and has enormous potential to transform the education sector. The present study was conducted to find out the constraints faced by the students in the usage of ICT initiatives in agricultural education. The collected constraints were analyzed using Garret’s ranking methodology to develop a quantitative position of each constraint. The findings showed that students face personal, infrastructural/ technical, and organizational constraints more severely. Among the personal constraints, the high cost of ICTs Tools/Gadgets, Lack of awareness about the availability of different ICT tools were prominent. Similarly, in the case of infrastructural/technical constraints Internet Speed/Connectivity and lack of up-gradation of ICT equipment dominated. In case of organizational constraints subscription of relevant Journals and e resources and lack of training on ICT tools ranked at top. Thus, several field-level constraints faced by agricultural students have been identified and ranked to the context for using ICT in education.